Temporal trends in the prevalence and causes of visual impairment in the South Indian state of Telangana: a population-based cross-sectional study - Srinivas Marmamula; Rohit C Khanna; Shashank Yellapragada; Rajesh Challa; Javed Mohd; Gullapalli Nageswara Rao (BMJ Open)
Objectives To investigate the temporal trends in the prevalence and causes of visual impairment (VI) in South India.Design Population-based cross-sectional studies conducted during the years 2011–2012 and 2017 using identical study methods and in geographical locations are compared. The L V Prasad Eye Institute established services in Khammam and not in Warangal district after the 2011–2012 study.Setting Khammam and Warangal districts in Telangana, India.Participants In total, 5357 participants aged ≥40 years were examined from two districts in the 2011–2012 study and 4923 participants were examined in the 2017 study.Main outcome measures Age-adjusted and gender-adjusted temporal trends in the prevalence and causes of VI.Blindness and moderate VI (MVI) were defined as presenting visual acuity worse than 6/60 and 6/18–6/60 in the better eye, respectively. VI included MVI and blindness.Results Nearly 2500 participants were examined in each location in both the 2011–2012 and 2017 studies. In Khammam district, overall VI declined by 2.5% from 15.5% to 13.0% (p<0.001). While there was no significant change in MVI (p=0.566), blindness declined by 3.0% from 5.4% to 2.4% (p<0.001). In Warangal district, the overall VI remained unchanged (p=0.60). While MVI increased by 3% from 9.3% to 12.3% (p=0.001), blindness declined by 3.5% from 6.5% to 3.0% (p<0.001). While MVI due to cataract increased in both districts, there was a significant decline in MVI due to refractive errors in Khammam.Conclusion There was a significant decline in VI in Khammam district but not in Warangal district. The differential trends in prevalence and causes of VI can be explained by the availability and uptake of eye care services in these two districts.